2020
DOI: 10.1016/j.jmpt.2019.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Investigation of Dorsal Neck Muscle Deformation During a Neck Rotation Exercise

Abstract: Objectives: Neck-specific exercise can reduce neck pain and increase function, but information on how different neck muscle layers are activated during neck exercises is scarce. The aim of this study was to investigate deformation and deformation rate in five dorsal neck muscles and correlation between these muscles during a loaded dynamic exercise used in clinical practice.Methods: Deformation and deformation rate were investigated in five dorsal right sided neck muscles in twenty individuals without neck pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Trial heterogeneity and small sample size makes it di cult to draw conclusions of neck muscle activation or mechanical function between studies. To our knowledge have only two study evaluated dynamic neck movement with speckle-tracking analyses 25,43 . Bjorklund et al showed highest deformation in contralateral Scap of ve investigated muscles during neck rotation in quadruped standing in individuals without neck pain 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trial heterogeneity and small sample size makes it di cult to draw conclusions of neck muscle activation or mechanical function between studies. To our knowledge have only two study evaluated dynamic neck movement with speckle-tracking analyses 25,43 . Bjorklund et al showed highest deformation in contralateral Scap of ve investigated muscles during neck rotation in quadruped standing in individuals without neck pain 43 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge have only two study evaluated dynamic neck movement with speckle-tracking analyses 25,43 . Bjorklund et al showed highest deformation in contralateral Scap of ve investigated muscles during neck rotation in quadruped standing in individuals without neck pain 43 . An isometric activation of the neck muscles in combination with rotation is needed in this position and the test position and resistance is different form the test in the present study.…”
Section: Discussionmentioning
confidence: 99%